Legal Protection of the Right to Indication of Origin in Indonesia - Masnun, Muhammad Ali (JOURNAL OF PRIVATE AND COMMERCIAL LAW, 2018)
The purpose of this study is to analyze the form of legal protection rights for indications of origin in Indonesia based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications (Trademark and GI Law). Legal protection rights for indications of origin are inseparable from consideration of the economic value inherent in a property. Indications of origin are different from geographical indications, indications of origin are signs that indicate the origin of goods or services that are not identical to natural (geographical) factors. This research is a normative juridical using primary legal materials and secondary legal materials, as well as using prescriptive analysis methods.The results of the study show that legal protection can be provided in the form of preventive and repressive legal protection, however, the legal protection regulation of rights for indications of origin in Indonesia are still relatively very low. Protection of rights for indications of the origin arises with a declarative system that cannot be separated from the rights to the trademark. The right to the trademark is a prerequisite for being able to declare the right to an indication of origin. The period of protection of rights for indications of the following ten years of protection of trademark and can be extended again. Transfer of rights to indications of origin is impossible to do because it is attached to the rights to the trademark and is different from the non-transferability as a geographical indication. Violation of rights for indications of origin can be in the form of use of indications of origin by non-registered users of trademark has been registered with indication of origin. The firmness of the government to provide legal protection in the form of statutory rights for indications of origin is an absolute necessity. The government must be present to provide a regulation as a consequence of the legal state, which means that in carrying out all tasks and activities, it must be based on applicable law.